Jaguar: Another Threatened Panther - Anthony J. Novack; Martin B. Main (EDIS)
This document is Fact Sheet WEC 167, one of a series of the Department of Wildlife Ecology & Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Originally published in cooperation with the Florida Fish and Wildlife Conservation Commission's Nongame Wildlife Program. Publication date: May 2003.